PSYCHOLOGICAL WELL-BEING AMONG INFORMAL CAREGIVERS CARING FOR PERSONS WITH DEMENTIA LIVING AT HOME - Lethin, C. (Innov Aging, 2017)
This study investigated informal caregivers’ psychological well-being and predicted increase in psychological well-being, when caring for persons with dementia (PwDs) living at home, related to caregiver, PwD and formal care (FC) factors. This was a cohort study, at baseline and follow-up in eight European countries. Caregivers included (n=1,223) were caring for PwDs aged ≥ 65 years living at home, in risk of being institutionalized. Data was collected using standardized instruments. Logistic regression analysis of factors associated with caregiver psychological well-being at baseline and 3 months later was performed. Factors associated with presence of caregiver psychological well-being at baseline were positive experience of caregiving, low caregiver burden, high quality of life (QoL) for caregivers, male gender of PwD, high QoL of PwD and few neuropsychiatric symptoms for the PwD. At follow-up, caregivers with increased psychological well-being experienced quality of care (QoC) higher and were more often using dementia specific service. Predicting factors for caregivers’ increased psychological well-being were less caregiver burden, positive experience of caregiving, less supervision of the PwD and higher caregiver QoL, if PwD were male, had higher QoL and less neuropsychiatric symptoms. Higher QoC predicted increased caregivers’ psychological well-being. It can be concluded that informal caregiving for PwDs living at home is a complex task. Our study showed that caregivers’ psychological well-being was associated with, among other things, less caregiver burden and higher QoL. Professionals should be aware of PwD neuropsychiatric symptoms that might affect caregivers’ psychological well-being, and provide proper care and treatment for caregivers and PwDs.